Evaluating the Categorisation of the Public Hospitals in Chile According to Case-Mix Complexity: A Genetic Algorithm Approach - Inostroza-Ponta, M; Villalobos-Cid, M (IEEE Computer Society, 2020)
The healthcare services must provide quality health safeguarding the efficient use of the resources. To evaluate technical efficiency performing fairly comparisons it is necessary to group the hospitals according to the type of patient treated: case-mix. Generally, this evaluation is performed by using the Related Groups for Diagnosis (DRG) system. Since only a few hospitals have implemented this system in Chile, the analysis of technical efficiency results limited the Ministry of Health of Chile (MINSAL) has proposed an administrative categorisation for the public hospitals: high, medium and low complexity. However, it has not been studied if this definition is associated to the case-mix and if it can be used to study technical efficiency. In this work, we propose an ad-hoc genetic algorithm which combines filter feature selection and clustering strategies to determine if there is a set of features related to the case-mix that allow to reach the same categorisation proposed by the MINSAL the results show that, although a small set of features is able to reach this categorisation by year, there is not enough evidence to establish a relationship with the case-mix. It is recommended that future technical efficiency analyses use new categorisations based on case-mix instead of the MINSAL categorisation. © 2020 IEEE.